STUDI IMPLEMENTASI PROYEK PENANGGULANGAN KEMISKINAN DI PERKOTAN (P2KP) - Widowati, Nina (JURNAL ILMU SOSIAL, 2007)
Urban Poverty Project (P2KP) as one of government projects with the aim of reconciling the poverty. The object of Urban Poverty Project as the poor society in urban area under the approved criterion. The objective of Urban Poverty Project as to give revolving fund to the target groups. The implementation of urban poverty project in Kedungmundu suberb is not distributed on proportion. Under the assumption, it possibly had some bearing on communication and awareness phenomena. The result of the researchshowed that the attainment of implementation of urban poverty project as influenced a lot by the society’s awreness that doesn’t support the execution as the procedure to develop the self-reliance society groups is not simple.